CERMINAN KEHIDUPAN SOSIAL MASYARAKAT DALAM NOVEL LASKAR PELANGI KARYA ANDREA HIRATA: KAJIAN SOSIOLOGI SASTRA - Isnaini, Isnaini; Marselinus Gito; Fitriah, Fitriah; Saptiana Sulastri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the reflection of social life in Andrea Hirata's novel Laskar Pelangi using a sociological approach to literature. This novel was chosen because it is able to represent the social reality of Belitung society, which is marked by various problems such as poverty, disparities in access to education, and the struggle to live amidst limitations. The method used in this study is a descriptive qualitative approach with data collection techniques through literature review and text analysis of the novel’s content. The results show that Laskar Pelangi reflects the social life of a community with economic limitations, yet one that continues to uphold the value of education as a means of social mobility and life transformation. In addition, the novel portrays strong social relationships within the community, characterized by solidarity, cooperation, and a high fighting spirit in facing various social challenges. On the other hand, it also depicts social inequality among certain groups, highlighting differences in access to resources, particularly in education. Thus, through a sociological approach to literature, the novel Laskar Pelangi functions not only as a work of fiction but also as a real reflection of social life filled with educational, moral, and inspirational values, thereby providing a deeper understanding of the relationship between literary works and social reality. Sociology of literature, social life, Laskar Pelangi, social reflection, education.